Navigating The Complexities of Mut’ah Marriages: The Role of West Java’s Local Government in Protecting Communities - Dadang Syaripudin; Encang Saefudin (Asy-Syari'ah, 2023)
Adultery is one of the reasons Islam pays excellent attention to marriage. The danger due to adultery is very great, as well as being categorised as a major sin that Allah SWT hates. Islam really expects all forms of adultery, let alone an act of adultery that is defended and justified and packed with values ​​that seem to be true. Mut'ah marriage, which often occurs in the peak tourist area, which is known as the "Arab village," is one of the justifications for the act of adultery. The research method used is normative-empirical. In addition, researchers employed a case-and-law approach to review findings from field observations obtained through interviews and other data-collection techniques. The results of this study suggest that contract marriages in the Puncak area, also known as Kampung Arab, are common; however, since the onset of the COVID-19 pandemic, they have decreased somewhat due to policies limiting activities across countries to curb the spread of COVID-19. The Cianjur Regency government is carrying out efforts to counteract the practice of mut'ah marriage by making a district regulation that specifically prohibits this practice. In addition, the role, awareness, and concern of the surrounding community remain strong in efforts to restore Cianjur's image as a city of students.